Sorption of Microconstituents onto Primary and Activated Sludge to which Alum Has Been Added - Zhu, Ying (Université d'Ottawa / University of Ottawa, 2014)
Microconstituents (MCs) have become an emerging concern to scientists and researchers. Due to the development of analytical technology, it is now possible to study MCs at ηg/L to μg/L levels. Wastewater treatment plants (WWTPs) are the major point source for MCs entering the environment based on the literature. WWTPs are known to be unable to remove many MCs to a safe level. In order to fully understand the fate of MCs in WWTPs and to further improve the design of WWTPs in terms of MC removal, it is necessary to examine removal mechanisms such as sorption and biodegradation in WWTPs. Three MCs, bisphenol A (BPA), 17-α-ethinylestradiol (EE2) and triclosan (TCS), were chosen for this study. They are chemicals reported to be hydrophobic and have low vapor pressure, which makes sorption a highly potential removal mechanism. Primary sludge and activated sludge (AS) were used to perform sorption kinetics and isotherm experiments for BPA, EE2 and TCS. Primary sludge was collected from local WWTPs, and AS was generated from a lab-scale continuous flow bioreactor system maintained at solids retention times of 15, 10 and 5 d and hydraulic retention time (HRT) of 6 h. Alum was added to synthetic wastewater influent at concentrations typically used for phosphorus removal at some plants. Alum has the potential to change sludge structure and influence the sorption process. A comparison was made with AS as the adsorbent with and without alum addition to the AS to study the influence of alum on the sorption processes. The selected MCs were found to reach sorption equilibrium with primary sludge within 7 h. A pseudo second-order kinetic model was an excellent fit to describe the sorption processes of selected MCs. The solids-liquid partitioning coefficient (Kd) was determined for the three chosen MCs. The Kd values found for primary sludge and AS are very close. The Kd for MCs sorbed to AS in this study were compared with the Kd for AS without alum addition. Although alum addition showed no influence on effluent soluble chemical oxygen demand, it decreases the Kd for BPA and EE2 sorbed to AS. In contrast, a much higher Kd for TCS was observed for AS with alum addition. Judging from the R2 values, the linear sorption model is not suitable for some of the isotherms. Langmuir and Freundlich sorption isotherms were further used to fit the experimental data by applying linear regression and nonlinear regression approaches. The Freundlich isotherm was found to be the most suitable model to describe the experiment data.
Keywords: microconstituents; alum; sorption; wastewater treatment